Compilation of epidemiological surveys in oral health in Brazil from 1986 to 2015: Main methodological aspects (Research, Society and Development, 2021)
Introduction: oral health epidemiological surveys use public policies as a subsidy, until the time when publications on a compilation of all surveys conducted in Brazil are not published. Objective: to compile all the methodologies used in the main epidemiological surveys on oral health carried out in Brazil between the years 1986 to 2015. Methods: compilation based on researches in books, periodicals, articles in LILACS, MEDLINE, BBO and SCIELO databases, as well as final reports of studies. Evaluations over the surveys carried out in the State of São Paulo in 1998, 2002 and 2015 as well as those carried out in the years 1986, 1993, 1996, 2003 and 2010 covering the entire country. Results: compiled the methodologies used were modifying themselves and expanding the scope of the problems studied. There is evidence of improvement in the elaboration of work procedures in epidemiological surveys, mainly in what refers to the coverage of the researched population, calibration and measurement of results. Conclusion: the advances in the methodological criteria on researches can be attributed to the strength of public policies regarding oral health that have been implemented in Brazil over the last decades. In addition, there is a constant participation of academic institutions in a growing process of interaction between scientific knowledge and practice.